Sustainable Air Purifiers for Thai Smart Cities: Integrating Circular Economy and Public Health in Municipal Innovation - Taghipour, Amirhossein; Saengnoree, Amnuay; Sangmanee, Woranat (My University, 2026)
Rapid urbanization and economic growth in Thailand have intensified urban air-quality challenges, especially PM2.5 pollution associated with agricultural burning, industrial emissions, and traffic congestion. Municipal governments are therefore exploring technological interventions that can complement conventional emission-control policies in the transition toward healthier smart cities. One promising approach is the deployment of sustainable outdoor air-purifier towers equipped with high-speed fans, jet scrubbers, and IoT-based monitoring systems. Early pilots, including the MQDC FahSai Mini tower, have demonstrated substantial dust-reduction potential and real-time data integration with public air-quality platforms. This study develops an interdisciplinary framework that connects public health, circular economy principles, technology adoption, and sustainable urban design. We examine how environmental awareness, perceived effectiveness, social influence, perceived cost, health anxiety, and value co-creation shape adoption intention and behavior toward municipal air-purification systems in Bangkok, Chiang Mai, Khon Kaen, and Phuket. Using mixed methods, including interviews and survey data from 320 stakeholders, residents, and officials, and analyzing the data through CFA and SEM, the study finds that environmental awareness and perceived effectiveness positively influence adoption, while perceived cost reduces it. Value co-creation emerges as the strongest driver of adoption intention and mediates the role of social influence. Scenario analysis further indicates that the deployment of 10–15 purifier towers could reduce PM2.5 by approximately 30–40% and generate meaningful health-related economic benefits. The discussion now more explicitly addresses the end-of-life management of saturated filter media, the role of multi-level governance and redistributive financing for urban equity, and the importance of addressing technological anxiety to secure a durable social license for deployment.
Keywords: Air quality; Circular economy; Environmental policy; IoT sensors; Public health; SEM; Smart cities; Sustainable air purifiers; Technology adoption; Thai municipalities